Advocating transmigrants through videos on the YouTube channel Asian Survivor - Sirait, Rinda Aunillah; Abdullah, Aceng (Universitas Padjadjaran, 2024)
Background: Revival Rival shares videos through the YouTube channel “Asian Survival.” The video is about the situation in the latest transmigrant location in Tanjung Buka Settlement Unit (SP) 10, Tanjung Palas Tengah District, Bulungan Regency, North Kalimantan. He practiced citizen journalism by raising topics that were not touched by the mainstream mass media. Purpose: This research aims to discover how Asian Survivor conducts advocacy through its citizen journalism video content. Methods: This is descriptive research using several data collection techniques, namely content analysis, interviews, and literature studies. Results: The Asian Survivor advocacy is carried out through the production of video content consisting of four topics, namely, donation distribution, human interest, actual information, and inspiring profile. In addition, Revival Rival manages donations from viewers touched by the news shared by maintaining accountability through a personalized reporting process. Conclusion: Asian Survivor is an advocacy media for new transmigrants in Tanjung Buka SP 10 through a variety of video content presented as a picture of the life struggles of new transmigrants in marginalized areas; social criticism presented implicitly to maintain media sustainability and to raise donations from netizens sent to help the lives of transmigrants. Raising netizen donations for charitable activities is a form of social media monetization. Implications: This research has implications for further research on the power of utilizing YouTube channels as advocacy media based on citizen journalism. Another research development is related to the ethical issues of raising donations made by YouTube content as another form of monetization of social media accounts.